CHOROIDAL THICKNESS CHANGES IN ACUTE ZONAL OCCULT OUTER RETINOPATHY. Issue 1 (January 2019) - Maehara, Hiroki; Sekiryu, Tetsuju; Sugano, Yukinori; Maruko, Ichiro
Abstract : Purpose: To investigate the longitudinal morphologic choroidal changes in eyes with acute zonal occult outer retinopathy. Methods: In this retrospective observational case series, we studied 10 patients (11 eyes) with unilateral acute zonal occult outer retinopathy at the first visit who were followed more than 12 months by enhanced depth optical coherence tomography. The retinal and choroidal thicknesses (CTs) were measured at six sites in the macula. Results: The integrity of the ellipsoid zone was lost 1, 500 μ m and 3, 000 μ m nasally in all 11 eyes at the first visit. Compared with the unaffected fellow eyes, the mean total retinal thickness at the first visit was significantly ( P = 0.03) thinner 3, 000 μ m nasal to the fovea in the affected eyes. The mean CTs in the affected eyes did not differ from that in the unaffected eyes at any evaluation; the mean subfoveal CT in the affected eyes gradually decreased during the follow-up period. Compared with the first visit, the mean subfoveal CT decreased significantly ( P = 0.011) at the foveal center and nasal, superior, and temporal to the fovea 12 months after disease onset. Conclusion: The subfoveal CT in eyes with acute zonal occult outer retinopathy can decrease during follow-up. Abstract : Changes in the choroidal morphology might occur during the course of acute zonal occult outer retinopathy in relation to inflammation associated with the disease.